2014
DOI: 10.1097/mao.0000000000000003
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic Implantation of the Human Vestibular System

Abstract: Hypothesis A functional vestibular prosthesis can be implanted in human such that electrical stimulation of each semicircular canal produces canal-specific eye movements while preserving vestibular and auditory function. Background A number of vestibular disorders could be treated with prosthetic stimulation of the vestibular end organs. We have previously demonstrated in rhesus monkeys that a vestibular neurostimulator, based on the Nucleus Freedom cochlear implant, can produce canal-specific electrically e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 25 publications
(39 reference statements)
1
65
0
5
Order By: Relevance
“…Identifying the more effective modulation paradigm has become increasingly relevant, as the concept of using modified cochlear implants has shown promise (Guyot et al 2011a(Guyot et al , 2011b and is being adopted also by other groups (Valentin et al 2013, Golub et al 2014, Phillips et al 2015. Cochlear implants use PAM per default for speech encoding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Identifying the more effective modulation paradigm has become increasingly relevant, as the concept of using modified cochlear implants has shown promise (Guyot et al 2011a(Guyot et al , 2011b and is being adopted also by other groups (Valentin et al 2013, Golub et al 2014, Phillips et al 2015. Cochlear implants use PAM per default for speech encoding.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic comparison of PAM and PRM has recently become increasingly necessary and urgent with the more widespread adoption of modified cochlear implants for vestibular stimulation (Valentin et al 2013, Golub et al 2014, Guinand et al 2015. The study herein is the first systematic comparison of both modulation paradigms in patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once established, BVH could be classified according to severity, taking not only objective measures but also functional impairment into account. A classification according to severity could be important, since much progress has been made in developing a vestibular implant [144,166,167,168] and such a classification could facilitate patient selection. If necessary, a subdivision into probability groups (e.g.…”
Section: Future In Diagnosing Bvhmentioning
confidence: 99%
“…In humans, extralabyrinthine and intralabyrinthine surgical routes to the lateral (LAN), posterior (PAN) and superior (SAN) ampullary branches of the vestibular nerve have been described and validated in peroperative stimulation trials [38,39,40,41,42,43]. Our group has reported on the results of the first chronic implantations of a vestibular implant prototype in human subjects [44], followed by a group at the University of Washington [45]. Our most recent results demonstrated that it is possible to elicit an artificial, motion-controlled vestibulo-ocular reflex in implanted patients [46].…”
Section: Introductionmentioning
confidence: 99%